An investigation on brainwave signal analysis while listening to sounds of nature by using a portable EEG device: a pilot study / Nurzatul Ain Roslan ... [et al.] - Roslan, Nurzatul Ain; Gopalan, Yogheswaran; Karuppannan, Mahmathi; Gnanasan, Shubashini (Faculty of Pharmacy, 2020)
Electroencephalogram (EEG) is a method of measuring the neuro-signals of the brain. Portable EEG device was used to measure the level of attention and meditation before and during listening to the sounds of nature. Listening to the sounds of nature may induce relaxation to the body and mind. The objectives of this study were to identify the differences in the level of attention and meditation before and during listening to the sounds of nature and also to determine whether there is a difference between males and females with regards to the level of attention and meditation. Thirty pharmacy students (15 males; 15 females) were involved in this study. Attention and meditation levels of the students before and during listening to the sounds of nature were recorded, analyzed and evaluated. The results showed that the mean score of attention was higher during listening to the sounds of nature meanwhile the mean score of meditation was lower. There were no significant differences in the level of attention and meditation between males and females.